Information Sharing Scheme Using AoI for DTN-based Evacuation System - Obayashi, Shoya; Ohta, Tomoyuki (International Journal of Networking and Computing, 2025)
In recent years, Japan has frequently experienced natural disasters such as earthquakes and typhoons, necessitating the rapid and accurate acquisition of evacuation support information. However, during such disasters, communication infrastructure may be damaged, making information sharing difficult. To address this issue, Delay/Disruption Tolerant Networking (DTN) technology has garnered attention. In this study, we propose a new information-sharing scheme for evacuation support systems using DTN. The proposed scheme leverages the Age of Information (AoI) to assess the freshness of information, discarding information that exceeds a certain AoI threshold. This ensures that evacuees can act based on the most recent and accurate information. Furthermore, by predicting the occupancy of evacuation centers in advance, the proposed scheme helps prevent situations where evacuation centers reach full capacity and can no longer accept evacuees, enabling a smoother evacuation process. Specifically, the scheme combines two prediction mechanisms: the first mechanism that estimates the number of evacuees based on the rate of increase information provided and transmitted by evacuation centers and the second mechanism that utilizes DTN to share estimated arrival times among evacuees to predict the number of evacuees in the destination evacuation center. This approach facilitates more appropriate selection of the destination evacuation center. We evaluate the effectiveness of the proposed scheme through simulation experiments using real geographical information. Additionally, we discuss the impact of the proposed scheme on evacuation time, the number of evacuees, and the average evacuation time. Consequently, it is confirmed that the proposed scheme could provide shorter evacuation time with evacuees.